HUBUNGAN ANTARA KEGIATAN SUPERVISI DENGAN PELAKSANAAN PATIENT SAFETY DI RUANG RAWAT INAP - Francisca, Riche "; Utami, Gamya Tri; ", Misrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractThis research aims to know the relationship between the activities of supervision with the implementation patient safety in ward of Sub Mandau Hospital. This research method used description correlation with cross sectional approach. The sample were 44 respondents by a total sampling technique. Measuring instrument used was a questionnaire for the supervision and implementation of activity variables patient safety. Analysis of the research were univariate and bivariat analysis. Univariate analysis related the age, sex, marital status, education, work and training in patient safety ever followed.  Bivariat analysis was conducted to look at the relationship between supervision activities with the implementation of patient safety with Chi Square test. Test results showed that the respondents who received good supervision activities 69.2% and respondents are implementing patient safety both of 38,9%. The Chi Square test results showed a P value = 0.066 > α = 0.05, with an Odds Ratio of 0.458 so it is not obtained by the relationship between the activities of supervision with the implementation of patient safety.  Based on the results of such research, it is expected the nurses to better improve implementation implementing patient safety especially in identifying patients to reduce the error the giving of services for patients so that patients get safe and avoid injury.Keywords              : supervision, implementation activities, patient safety